Religious Education of the Child as Part of Parental Duties - Comparative Legal Analysis of National Reports Submitted to the Commission on European Family Law - Marta Prucnal-Wójcik (Ignatianum University Press, 2024)
Research objectives and problems: This article presents a comparative analysis of legal regulations in 21 European countries regarding parents' rights and obligations towards their children's religious education and upbringing. The author seeks answers to the following questions: Does religious upbringing and education of the child fall under parental rights and duties? What is the legal basis for this right and duty? Does a child have the right to choose his or her religion? Research methods: The author carries out legal analysis of reports from 21 countries concerning parental responsibility, submitted to the Commission on European Family Law. Structure of the article: By analyzing the provisions in the internal legislation of 21 European countries, based on reports submitted to the Commission on European Family Law, the author presents the legal solutions regulating issues of children's religious upbringing. Research findings and their impact on the development of educational sciences: The analysis indicates that in each of the 21 legal systems examined, religious upbringing of the child is considered an element of parental responsibility. The most common legal sources for parental rights to a child's religious upbringing are constitutions, civil codes, and legal acts on family/children's rights, education, and freedom of religion. National legislation typically grants parents the exclusive right to decide on their child's religious upbringing for younger children. As the child matures, their right to self-determination in religious matters increases. The study shows that, despite national cultural and ideological differences, European countries have more in common than divides them regarding religious education of children within the context of parental responsibility. This study expands our understanding of the shared European belief among legislators about the appropriateness of entrusting such an important task as the religious upbringing of a child to the child's parents. Conclusions and/ or recommendations: The presented considerations offer a general overview of the regulations in individual countries and serve as an introduction to a more in-depth analysis of the issue of religious upbringing of the child. Further research is needed to examine other aspects of religious upbringing, such as religious education in schools and possible legal remedies in case of conflicts between parents, parents and children, or families and the state.